Utilizing Technology in Multicultural Education: Experiences from Canadian Schools - Emma Clark; James Scott; Olivia Davis (Yayasan Adra Karima Hubbi, 2025)
Background. In the context of increasingly diverse classrooms, Canadian schools face both the challenge and opportunity of fostering inclusive learning environments through multicultural education. As technology becomes more integrated into pedagogy, its role in addressing linguistic, cultural, and social differences gains prominence. Purpose. This study explores how educators in Canadian schools utilize digital tools to support multicultural education and promote equity among students from diverse backgrounds. The research aims to identify effective strategies, tools, and practices that enhance cultural inclusivity and student engagement through technology-enhanced instruction. Method. A qualitative multiple-case study approach was employed, involving interviews with 28 teachers, classroom observations across six schools, and analysis of institutional technology integration plans. Results. The findings indicate that technology, when used intentionally, facilitates culturally responsive teaching through language support apps, collaborative platforms, and digital storytelling tools. However, the study also reveals disparities in access, digital literacy, and institutional readiness, which hinder equitable outcomes. Conclusion. The study concludes that leveraging technology for multicultural education requires not only pedagogical innovation but also systemic support, teacher training, and inclusive design principles. These insights offer practical implications for educators and policymakers seeking to enhance diversity and inclusion in digital learning environments.